Bridge jobs in Europe - Brunello, Giorgio; Langella, Monica (Bonn, 2012)
"We study the transitions from career to bridge jobs and to permanent retirement by European males aged 55 to 70 at the time of the interview in the late 2000s. We find that only 10.54 percent of the workers in our sample who were in a career job at age 50 have moved to a bridge job by the time of the interview, much less than what usually found in the United States. We also show that the exogenous increases in minimum retirement age that occurred during the past twenty years have had different effects in Central / Northern Europe (Austria, Switzerland, The Netherlands and Sweden) and in Mediterranean Europe (Italy and Spain). In the North, transitions into bridge jobs have increased, with no significant effect on transitions into retirement. In the South, transitions into permanent retirement have decreased, with no significant effect on transitions into bridge jobs."